2017
DOI: 10.18203/2320-6012.ijrms20175468
|View full text |Cite
|
Sign up to set email alerts
|

Role of leukocyte free platelet rich plasma in planter fasciitis: a prospective study

Abstract: Background: Planter fasciitis, is by definition, inflammation of planter fascia. Most of the cases are well treated conservatively and a few responds to surgery only. Objectives of present study were evaluating the efficacy of a single injection of leukocyte free platelet rich plasma in plantar fasciitis and to derive a correlation between the clinical and radiological outcome.Methods: The present study consisted of 120 patients of bilateral (PF), (240 feet). These patients were divided into two groups PRP gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated the clinical effectiveness of both PRP and ESWT in the management of PF. 2,9,12,16,21,31,32,40 However, our results show that PRP was superior in reducing pain outcomes when compared with ESWT. In fact, 6 of the 7 analyzed studies 6,11,13,27,33,38 showed better pain improvement in the PRP group, with the remaining study showing no significant differences between PRP and ESWT.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Previous studies have demonstrated the clinical effectiveness of both PRP and ESWT in the management of PF. 2,9,12,16,21,31,32,40 However, our results show that PRP was superior in reducing pain outcomes when compared with ESWT. In fact, 6 of the 7 analyzed studies 6,11,13,27,33,38 showed better pain improvement in the PRP group, with the remaining study showing no significant differences between PRP and ESWT.…”
Section: Discussioncontrasting
confidence: 57%
“…3,41 Previous studies present in the literature have reported the safety and efficacy of PRP in the treatment of recalcitrant PF, demonstrating its superiority when compared to placebo. 31,32 Extracorporeal shock wave therapy (ESWT) is another alternative noninvasive therapy option for tendon and musculoskeletal pathologies, including PF. Although the exact mechanism is not fully understood, it is postulated that use of pulsed acoustic sound waves contributes to the healing of degenerated or inflamed plantar fascia by stimulating neovascularization and collagen synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells contain anti-inflammatory and pro-inflammatory cytokines that can affect the final outcome differently. While the former can help prevent infection [44,48], the latter may trigger local inflammatory reactions and enhance pain [42,49]. Accordingly, there seems to be no agreement on whether to use PRP low in leukocytes or not.…”
Section: Originalmentioning
confidence: 99%